2010
DOI: 10.1681/asn.2009111186
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of WNK1 Expression by miR-192 and Aldosterone

Abstract: WNK1 and WNK4 encode two members of the WNK serine-threonine kinase subfamily. Greater WNK1 expression associates with higher BP. A combination of promoters, enhancers, repressors, and insulators regulate WNK1 expression, but whether microRNAs also modulate WNK1 expression is unknown. Here, computational analysis revealed the presence of a target sequence for miR-192 and miR-215 at the same site in the 3Ј untranslated region of the ubiquitous L-and the kidney-specific KS-WNK1. We functionally validated this ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…We could identify miR-29b as an aldosterone-dependent miR and subsequently investigated the regulatory mechanism and the potential relevance for vascular pathology per se and for aldosterone-mediated effects in particular. Recently, the MR has been described to regulate miRs involved in physiologic renal MR functions such as salt and water homeostasis (43,44). We were able to identify miR29b as an aldosterone-sensitive "target" that is reduced in abundance in the presences of the hormone in vivo in aorta, primary VSMCs and VSMC lines, but not in endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…We could identify miR-29b as an aldosterone-dependent miR and subsequently investigated the regulatory mechanism and the potential relevance for vascular pathology per se and for aldosterone-mediated effects in particular. Recently, the MR has been described to regulate miRs involved in physiologic renal MR functions such as salt and water homeostasis (43,44). We were able to identify miR29b as an aldosterone-sensitive "target" that is reduced in abundance in the presences of the hormone in vivo in aorta, primary VSMCs and VSMC lines, but not in endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have begun to address the emerging role of miRNAs in regulating ion transport in the distal nephron. Elvira-Matelot et al (13) have demonstrated that low Na ϩ feeding, high K ϩ feeding, or chronic aldosterone infusion of mice decreases renal miR-192 expression. The authors have suggested that aldosterone inhibits miR-192 expression as mechanism for increasing WNK1 (with-no-lysine kinase-1) expression in the CCD; since WNK1 regulates a number of ion transporters and channels in the distal nephron (19,26,35,38), the authors propose that miR-192 partly mediates the regulatory effects of aldosterone and WNK1 on ion transport in the CCD (13).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of miR-466g was normalized to expression of the control miRNA sno-202. The small nucleolar RNA sno-202 was used as a loading control because expression of this miRNA is unchanged with aldosterone stimulation in mouse kidney (13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations